2007
DOI: 10.3748/wjg.13.6588
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of D-dimer for portal vein thrombosis after portal hypertension surgery in hepatitis B virus-related cirrhosis

Abstract: AIM:To evaluate the predictive value of D-dimer as a predictive indicator of portal vein thrombosis (PVT) after portal hypertension surgery in hepatitis B virus-related cirrhosis. METHODS:A prospective study was carried out in 52 patients who had undergone surgery for portal hypertension in hepatitis B virus-related cirrhosis. Changes in perioperative dynamic D-dimer were observed. The sensitivity, specificity, positive predictive values and negative predictive values of D-dimer were calculated, and ROC curves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Portal vein thrombosis (PVT) is a common adverse event of liver cirrhosis, and its incidence increases as liver disease progresses and is even higher in patients with various portal hypertension procedures [1][2][3]. Patients with acute and severe PVT may experience symptoms, such as fever, abdominal pain, ascites, and splenomegaly, but many patients do not exhibit symptoms in the early stage of onset [4].…”
Section: Introductionmentioning
confidence: 99%
“…Portal vein thrombosis (PVT) is a common adverse event of liver cirrhosis, and its incidence increases as liver disease progresses and is even higher in patients with various portal hypertension procedures [1][2][3]. Patients with acute and severe PVT may experience symptoms, such as fever, abdominal pain, ascites, and splenomegaly, but many patients do not exhibit symptoms in the early stage of onset [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that analyzed the relation and prognostic role of D-dimers in these patients confirmed significant association between the elevated D-dimers and the occurrence of PVT [153,154]. One study suggested that the risk of developing PVT in patients with liver cirrhosis was significantly higher in case of a significant postoperative rise in the D-dimers concentration that exceeded 16,000 ng/ml [153]. Zhang et al confirmed significant association between the elevated D-dimers and the occurrence of PVT independent of the CTP score [154].…”
Section: The Relation Between Endothelial Dysfunction Systemic Inflamentioning
confidence: 85%
“…On the other hand, the relation between elevated D-dimers and PVT in cirrhotic patients has also been evaluated. Most studies that analyzed the relation and prognostic role of D-dimers in these patients confirmed significant association between the elevated D-dimers and the occurrence of PVT [153,154]. One study suggested that the risk of developing PVT in patients with liver cirrhosis was significantly higher in case of a significant postoperative rise in the D-dimers concentration that exceeded 16,000 ng/ml [153].…”
Section: The Relation Between Endothelial Dysfunction Systemic Inflamentioning
confidence: 98%
“…The portal thrombosis and obstruction decreases the amount of blood flow to the liver, increases the encephalopathy rate, and accelerates the hepatic damage [11]. Reported postoperative thrombosis rates in the portal vein were 5.8-33.6% [41][42][43] and this rate was an important prognostic factor for portal hypertension in cirrhosis [44,45]. In our experience, the longterm patency rate reached 94.9% and only 4 patients had thromboses in the modified splenocaval stoma.…”
Section: Discussionmentioning
confidence: 99%